Serafina and the Twisted Staff - Beatty, Robert, 1963- (Disney·Hyperion, 2016)
In 1899, when an evil threatens all the humans and animals of the Blue Ridge Mountains, twelve-year-old Serafina, rat catcher for the Biltmore estate and the daughter of a shapeshifting mountain lion, must search deep inside herself and embrace the destiny that awaits her.